Hubungan Gangguan Citra Tubuh dengan Tingkat Stres Pasien Pasca Operasi Sectio Caesaria (SC) di Ruang Madinah Rumah Sakit PKU Muhammadiyah Sekapuk - Adi Nugraha Syahputra; Widiharti Widiharti (Wiraraja Medika : Jurnal Kesehatan, 2023)
Caesarean section surgery often causes psychological problems in patients, namely fear that has an impact on anxiety which can cause a decrease in the condition of reproductive disorders, disruption of blood flow, comfort, pain. Personality image, and the way people see themselves affects the psychological aspect. A realistic and consistent self-image will also give them a steady capacity for awareness, which will help them succeed in life. In the research conducted, this type of Analytical Descriptive was applied through a cross-sectional approach. The independent variable in this study is body image. The dependent variable applied to the study uses stress levels. The study population was all patients who underwent Caesarian Section (SC) deliveries at PKU Muhammadiyah Sekapuk Hospital. Part of the research sample was secaria patients, non-probability sampling technique with purposive sampling of the study sample. The sample size is 24 post-cesarean section (SC) patients. statistical test using spearman rank. The body image of post SC patients at PKU Muhammadiyah Sekapuk Hospital is dominated by negative 70.8%. The stress level of post SC patients at PKU Muhammadiyah Sekapuk Hospital is quite dominant at 45.8%. The results of the Spearman rank test p = 0.008 <0, there is a link between body image disturbance and the stress level of post SC patients at PKU Muhammadiyah Sekapuk Hospital